2022
DOI: 10.1186/s12962-022-00337-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of loss due to pharmaceutical fraud: evidence from the U.S.

Abstract: Background Globally and in the U.S. in particular, pharmaceutical fraud account for a large number out of all crimes in health care, which result into severe costs to the society. The Academy of Managed Care Pharmacists (Fraud, waste, and abuse in prescription drug benefits. 2019. Posted May 20. https://www.amcp.org/policy-advocacy/policy-advocacy-focus-areas/where-we-stand-position-statements/fraud-waste-and-abuse-prescription-drug-benefits.) estimate that pharmacy fraud is 1% of costs, theref… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The results also emphasize the need for more stringent regulations regarding the disclosure of FCOI in media and social networking services [36]. Considering the potential subconscious influence of FCOI on medical professionals' decisions, there is a call for transparency in financial relationships, significantly when such influence can shape public policies and opinions [37,38].…”
Section: Discussionmentioning
confidence: 91%
“…The results also emphasize the need for more stringent regulations regarding the disclosure of FCOI in media and social networking services [36]. Considering the potential subconscious influence of FCOI on medical professionals' decisions, there is a call for transparency in financial relationships, significantly when such influence can shape public policies and opinions [37,38].…”
Section: Discussionmentioning
confidence: 91%
“…Whilst, people with insurance are expected to spend less on medicine, health insurance in Iran does not significantly reduce the burden. Weaknesses in the insurance support system can lead to OCT medicine supply and self-medication resulting in physical complications [ 50 ]. In general, treatment goals selection, patient education, generic medicines utilization and female heads empowerment are among the basic measures to reduce pharmaceutical expenditure [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Designated private hospitals and designated primary medical institutions were the main agencies generating insurance fraud. Some studies reported on similar types of health care fraud in private hospitals in other countries and highlight the risks and management costs that insurance fraud poses to private hospitals (10,(60)(61)(62). But in China, medical insurance funds are usually managed by government departments.…”
Section: Discussionmentioning
confidence: 99%
“…Global Health Care Anti-Fraud Network estimated that $260 billion, ~6% of global health care spending is lost due to fraud each year ( 8 ). The United States accounts for 3–10% of its health care expenditures each year caused by fraud claims and medical abuse, costing between $100 and $300 billion ( 9 , 10 ). The NHS Fraud Authority (NHS CFA) predicted that in the UK the NHS costs around £1.27 billion due to moral hazards such as fraud annually ( 11 ).…”
Section: Introductionmentioning
confidence: 99%